A facile method to synthesize high‐molecular‐weight biobased polyesters from 2, 5‐furandicarboxylic acid and long‐chain diols. Issue 22 (25th June 2015) - Tsanaktsis, Vasilios; Papageorgiou, George Z.; Bikiaris, Dimitrios N.
ABSTRACT In this study, biobased furan dicarboxylate polyesters have been prepared using 2, 5‐furandicarboxylic acid (FDCA) and diols with high number of methylene groups (long‐chain diols), namely, 8, 9, 10, and 12. Because of the high boiling points of these diols, a modified procedure of the well‐known melt polycondensation was applied in this work. According to this, the dimethyl ester of FDCA (DMFD) reacted in the first transesterification stage with the corresponding diols forming bis‐hydroxy‐alkylene furan dicarboxylates (BHFD). In the second stage, the BHFD reacted with DMFD again at temperatures of 150–170 °C (for 4–5 h), and in the final stage, the temperature was raised to 210–230 °C (vacuum was applied for 2–3 h). The molecular weight of the polyesters and the content of oligomers, as was verified by gel permeation chromatography analysis, depend on the polycondensation time and temperature. The chemical structure of the polyesters was verified from 1H NMR spectroscopy. All the polymers were found to be semicrystalline, with melting temperatures from 69 to 140 °C depending on the diol used. In addition, the mechanical properties also varied with the type of diol. The higher values were observed for poly(octylene 2, 5‐furanoate), whereas the lowest values were observed for poly(dodecylene 2, 5‐furanoate) with the higher number of methylene groups in its repeating unit. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 2617–2632